Which government interventions are good in alleviating credit market failures? - Karel Janda (Charles University in Prague, Institute of Economic Studies (IES), 2008)
Credit contracting between a lender with a market power and a small start-up entrepreneur may lead to a rejection of projects whose expected benefits are higher than their total costs when an adverse selection is present. This inefficiency may be eliminated by a government support in the form of credit guarantees or subsidies. The principal-agent model of this paper compares different forms of government support and concludes that a guarantee defined as a proportion of a gross interest rate is not a sufficiently robust policy instrument. Lump-sum guarantees and interest rate subsidies are evaluated as better instruments because they have a nonambiguous positive effect on a social efficiency since they enable funding of socially efficient projects which would not be financed otherwise.
Keywords: D82; G18; H25; 330; information asymmetry; credit; guarantees; subsidies; Kreditmarkt; Bankgarantie; Subvention; Kreditpolitik; Asymmetrische Information; Theorie